Effect of Technology Towards Performance Through Work Stress in Land Agency Riau Island - Olenka, Rangga Ikrar Gombang; Wibisono, Chablullah; Khaddafi, Muammar (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Many factor believed to be affecting job performance like Technology, Organizational Support, Individual Characteristics, Individual Adaptability. But what if those factor are mediating by another factor, like work stress?. This study used the quantitative Method with Analysis Tool using AMOS version 24. The population in this study were all state civil servants in the Regional Office of the National Land Agency and the Land office in Riau Islands Province, totaling 266 people and sampling technique by using Slovin and got 160 people. The result showed that Technology negatively influence work stress, Organizational support positively influence work stress, no significant influence of individual characteristics toward work stress, Individual adaptability positively work stress, Work stress has a significant positive direct influence on employee performance, Technology shows a significant positive direct influence on performance, there is no significant direct influence between organizational support and performance, Individual characteristics have a significant negative direct influence on performance, there is no significant direct influence between individual adaptability and employee performance. For mediating testing, work stress does not mediate the influence of technology on employee performance or individual characteristics on employee performance; rather, it fully mediates the influence of organizational support on performance and individual adaptability on employee performance. Square Multiple Correlation for Work Stress = 100% and Performance = 68,3%. This research indicates that work stress at a certain level will greatly improve various aspects of employee performance and give new insight into the positive impact of work stress.